New mosquito records (Diptera: Culicidae) from northwestern Argentina - Linares, Mario Alfredo (2016)
The geographic distributions of Aedes casali, Ae. meprai, Culex acharistus, Cx. bidens, Cx. coronator, Cx. dolosus, Cx. saltanensis, Cx. imitator, Haemagogus janthinomys and Psorophora cyanescens are extended. This contribution updates the mosquito fauna listed for Argentina, increasing the number of species for the provinces of Jujuy, La Rioja and Santiago del Estero from 55 to 62, 22 to 25 and 25 to 26, respectively. Data on collection localities, habitat of immature stages, and health importance are also presented.